2011
DOI: 10.1097/fjc.0b013e3182010a96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Cyclooxygenase-2 and Nonselective Cyclooxygenase Inhibition on Myocardial Function and Perfusion

Abstract: Non-selective NSAIDs and selective cyclooxygenase-2 (COX-2) inhibitors are purported to increase adverse cardiovascular events. We hypothesized COX-2 inhibitors would alter myocardial blood flow, microvascular reactivity, oxidative stress, and prostaglandin levels. Adult Yorkshire swine were divided into three groups: no drug (control, n=7), a non-selective COX inhibitor (naproxen 400mg daily, NAP, n=7), or a selective COX-2 inhibitor (celecoxib 200mg daily, CBX, n=7). After 7 weeks physiologic measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Similar experiments by our lab on nonischemic myocardium and normocholesterolemic animals did not demonstrate such pronounced improvements in microvascular function with COX inhibition (21,22). The combination of hypercholesterolemia and chronic ischemia seems to create an environment that is particularly susceptible to the beneficial effects of COX-2 inhibition.…”
Section: Discussionsupporting
confidence: 54%
“…Similar experiments by our lab on nonischemic myocardium and normocholesterolemic animals did not demonstrate such pronounced improvements in microvascular function with COX inhibition (21,22). The combination of hypercholesterolemia and chronic ischemia seems to create an environment that is particularly susceptible to the beneficial effects of COX-2 inhibition.…”
Section: Discussionsupporting
confidence: 54%
“…MPO mediates peroxidation of chloride ions to form hypochlorous acid, which can directly damage lung epithelial and endothelial cells. MPO is also a significant source of tyrosine nitration, which can evoke protein conformational changes and damage to cell membranes [32, 33]. Evidence suggests that MPO promotes oxidation and nitrification during ischemia and reperfusion [34].…”
Section: Discussionmentioning
confidence: 99%
“…Various NSAIDs can inhibit tumor growth by drastically reducing their vascularization ( 29 ). This effect is generated when endothelial cell apoptosis is induced ( 30 ), or through the reduction of vascular endothelial growth factor (VEGF) levels - one of the principal angiogenesis inducers ( 31 33 ). In addition it has been reported that AKR1C3 overexpression promotes angiogenesis and aggressiveness of PCa cells (PC3), suggesting that AKR1C3-inhibition would reduce angiogenesis.…”
Section: Discussionmentioning
confidence: 99%